Synthesis of Thinned Linear and Planar Antenna Arrays, Using a Taguchi-Enhanced Binary Gold Rush Optimizer - Kong, Weibin; Zong, Yiming; Wang, Lei; Yang, Wenwen; Liu, Botong; Sun, Binghe; Zhou, Feng (Applied Computational Electromagnetics Society Journal (ACES), 2026)
In this paper, a Taguchi-enhanced binary gold rush optimizer (TEBGRO) is proposed for designing thinned antenna arrays with a low peak sidelobe level (PSLL). The method integrates the Taguchi orthogonal experimental design into the population initialization phase, generating high-quality initial populations to improve convergence speed and stability. By combining a differential mutation interference factor and a time-varying transfer function, the algorithm further balances global exploration and local exploitation capabilities. Experimental results show that TEBGRO outperforms other binary optimization algorithms for both 100-element linear arrays and 20 x 10 planar arrays.